Establishing the influence of the in-house water distribution system and sampling procedures on the microbiological quality of drinking water - Harlander, Dušan (Zdravniški vestnik, 2005)
Background. The purpose of this study was to find out how the in-house water distribution system affects the microbiological quality of drinking water and to find a suitable way to evaluate the results of microbiological tests according to the sampling locations, develop methods for establishing the influence of the in-house water distribution system on the quality of drinkingwater and evaluate the suitability of some procedures for sampling. Methods. The study was conducted in south-eastern Slovenia between October 2003 and October 2004, thereby eliminating the influence of the seasons. Four-hundred-and-sixty-eight samples of drinking water were included in the study. Results. The results of the samples included in this study suggest (p>0.05) that the first flush samples do not contain Escherichia coli more often than the samples after flushing and the sample from the primary water distribution system.The results also show that the heterotrophic plate count is significantly higher in the first flush samples (p<0.001). Conclusions. Thestudy demonstrated that the in-house water distribution system affects the microbiological quality of drinking water; and that certain sampling methods significantly affect the test results, and also that knowing the characteristics of the sampling locations is also of significant importance. Some results cannot be analyzed well, therefore additional research is needed.
Keywords: Colony Count, Microbial; Enterobacteriaceae; Escherichia Coli; Kolonija, štetje mikrobov; Letni časi; microbiology; mikrobiologija; pitna voda; Seasons; Specimen Handling; voda; Voda, mikrobiologija; Voda, onesnaževalci; Voda, preskrba; vodovodno omrežje; Vzorec, ravnanje; Water Microbiology; Water Pollutants; Water Supply